2022
DOI: 10.3389/fendo.2022.959089
|View full text |Cite
|
Sign up to set email alerts
|

Positive BRAFV600E mutation of primary tumor influences radioiodine avidity but not prognosis of papillary thyroid cancer with lung metastases

Abstract: PurposeThis study investigated the relationship between BRAFV600E mutation of the primary tumor and radioiodine avidity in lung metastases (LMs) and then further evaluated the impact of BRAFV600E mutation and radioiodine avidity status on the prognosis of papillary thyroid cancer (PTC) with LMs.MethodsNinety-four PTC patients with LMs after total thyroidectomy and cervical lymph node dissection between January 2012 and September 2021 were retrospectively included. All patients received BRAFV600E mutation exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In THCA, the BRAF V600E mutation is the most frequent somatic mutation site. The BRAF V600E mutation has been confirmed as an independent factor influencing the radioiodine avidity of PTC with lung metastases ( 8 ). Evidence has demonstrated that a single BRAF V600F mutation is not related to the prognosis of THCA; however, cooperation with other factors may lead to poor THCA outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In THCA, the BRAF V600E mutation is the most frequent somatic mutation site. The BRAF V600E mutation has been confirmed as an independent factor influencing the radioiodine avidity of PTC with lung metastases ( 8 ). Evidence has demonstrated that a single BRAF V600F mutation is not related to the prognosis of THCA; however, cooperation with other factors may lead to poor THCA outcomes.…”
Section: Introductionmentioning
confidence: 99%